From Blocking Shots to Blocking GI Transit, This Professional Basketball Player Does It All: A Case Report on Small Bowel Obstruction - Emily L. DeMaio; Richard C. Jarvis; Jessica A. Cohen; Courtney N. Gleason (Case Reports in Medicine, 2021)
Small bowel obstructions (SBO) are a commonly encountered diagnosis within emergency departments. Typically, these patients have evident risk factors including, but not limited to, prior abdominal surgery, personal or family history of gastrointestinal disorders, femoral and inguinal hernias, or neoplasm. In this case, we describe an SBO in a female, professional athlete whose swift, severe symptom onset, rapid resolution with conservative treatment, lack of identifiable risk factors, and prompt return to high level competition without recurrence are certainly unique. A female professional basketball player in her mid-20’s with no past medical history presented with a seven-hour history of worsening abdominal pain beginning in the epigastric region and migrating to the right lower quadrant. Physical exam did not reveal abdominal distension, tympany to percussion, or high-pitched bowel sounds. Initial differential diagnosis included appendicitis, ruptured ectopic pregnancy, and other genitourinary pathology. Computed tomography with contrast revealed distended loops of small bowel with wall thickening, enhancement, and decompressed loops of bowel distally, consistent with an SBO. Symptoms resolved after 24 hours with conservative treatment, including decompression with a nasogastric tube. The athlete returned to full participation five days after initial presentation without recurrence of symptoms. Outpatient gastroenterology workup was negative for predisposing conditions. This presentation is rare in the absence of bowel pathology, family history, or prior abdominal surgery. Perhaps, her profession as an athlete, with frequent air travel and extensive exercise, may have contributed to this unique presentation. This case report should serve as a reminder to all providers that SBOs can occur in young, active patients devoid of risk factors. Even in the absence of typical signs on physical examination, providers should use imaging as adjuncts based on their clinical gestalt and utilize conservative management, when appropriate, to maximize chances of recovery with minimal morbidity.